(untitled) (Journal of Partial Differential Equations, 2018)
In this paper, we use a recentworks [9], where the authors provide a newapproach for pseudo almost periodic solution under themeasure theory, under Acquistpace-Terreni conditions, we make extensive use of interpolation spaces and exponential dichotomy techniques to obtain the existence of μ-pseudo almost periodic solutions to some classes of nonautonomous partial evolution equations.